A novel method for in situ synthesis of SERS-active gold nanostars on polydimethylsiloxane film. Issue 37 (24th April 2017) - Fortuni, B.; Fujita, Y.; Ricci, M.; Inose, T.; Aubert, R.; Lu, G.; Hutchison, J. A.; Hofkens, J.; Latterini, L.; Uji-i, H.
Abstract : A one-step method to form gold nanostars on a polydimethylsiloxane film is proposed for highly-sensitive SERS substrates. Abstract : A novel one-step in situ synthesis of gold nanostars (AuNSs) on a pre-cured polydimethylsiloxane (PDMS) film is proposed for the fabrication of highly sensitive surface-enhanced Raman scattering (SERS) substrates. Plasmonic activity of the substrates was investigated by collecting SERS maps of 4-mercaptobenzoic acid (4-MBA). The applicability of these flexible substrates is further demonstrated by SERS-based pesticide detection on fruit skin.